Functional characterization of residues involved in redox modulation of maize photosynthetic NADP-Malic enzyme activity - Alvarez, Clarisa Ester (2012)
Two highly similar plastidic NADP-malic enzymes (NADP-MEs) are found in the C 4 species maize (Zea mays); one exclusively expressed in the bundle sheath cells (BSCs) and involved in C 4 photosynthesis (ZmC 4-NADP-ME); and the other (ZmnonC 4-NADP-ME) with housekeeping roles. In the present work, these two NADP-MEs were analyzed regarding their redox-dependent activity modulation. The results clearly show that ZmC 4-NADP-ME is the only one modulated by redox status, and that its oxidation produces a conformational change limiting the catalytic process, although inducing higher affinity binding of the substrates. The reversal of ZmC 4-NADP-ME oxidation by chemical reductants suggests the presence of thiol groups able to form disulfide bonds. In order to identify the cysteine residues involved in the activity modulation, site-directed mutagenesis and MALDI-TOF (matrix-assisted laser desorption ionization-time of flight) analysis of ZmC 4-NADP-ME were performed. The results obtained allowed the identification of Cys192, Cys246 (not conserved in ZmnonC 4-NADP-ME), Cys270 and Cys410 as directly or indirectly implicated in ZmC 4-NADP-ME redox modulation. These residues may be involved in forming disulfide bridge(s) or in the modulation of the oxidation of critical residues. Overall, the results indicate that, besides having acquired a high level of expression and localization in BSCs, ZmC 4-NADP-ME displays a particular redox modulation, which may be required to accomplish the C 4 photosynthetic metabolism. Therefore, the present work could provide new insights into the regulatory mechanisms potentially involved in the recruitment of genes for the C 4 pathway during evolution. © 2012 The Author.